Guizhi Fuling Wan as a Novel Agent for Intravesical Treatment for Bladder Cancer in a Mouse Model - Chi-Chen Lu; Cheng-Huang Shen; Chia-Bin Chang; Hsiao-Yen Hsieh; Jiann-Der Wu; Ling-Huei Tseng; Dennis W Hwang; Syue-Yi Chen; Shu-Fen Wu; Michael W Y Chan; Cheng-Da Hsu (BMC, 2016)
Abstract Alternative intravesical agents are required to overcome the side effects currently associated with the treatment of bladder cancer. This study used an orthotopic bladder cancer mouse model to evaluate Guizhi Fuling Wan (GFW) as an intravesical agent. The effects of GFW were compared with those of mitomycin-C (Mito-C) and bacille Calmette-Guérin (BCG). We began by evaluating the response of the mouse bladder cancer cell line MB49 to GFW treatment, with regard to cell viability, cell cycle progression and apoptosis. MB49 cells were subsequently implanted into the urothelial walls of the bladder in female C57BL/6 mice. The success of the model was confirmed by the appearance of hematuria and tumor growth in the bladder. Intravesical chemotherapy was administered in accordance with a published protocol. In vitro data revealed that GFW arrested MB49 cell cycle in the G0/G1 phase, resulting in the suppression of cell proliferation and induced apoptosis. One possible mechanism underlying these effects is an increase in intracellular reactive oxygen species (ROS) levels leading to the activation of ataxia telangiectasia-mutated (ATM)/checkpoint kinase 2 (CHK2) and ATM/P53 pathways, thereby mediating cell cycle progression and apoptosis, respectively. This mouse model demonstrates the effectiveness of GFW in the tumor growth, with results comparable to those achieved by using BCG and Mito-C. Furthermore, GFW was shown to cause only mild hematuria. The low toxicity of the compound was confirmed by a complete lack of lesions on bladder tissue, even after 10 consecutive treatments using high concentrations of GFW. These results demonstrate the potential of GFW for the intravesical therapy of bladder cancer.